Phase Transition Thermodynamics of 1,3,5-Tris-(α-naphthyl)benzene: Theory and Experiment - Mikhail I. Yagofarov; Dmitrii N. Bolmatenkov; Airat A. Notfullin; Andrey A. Sokolov; Ilya S. Balakhontsev; Timur A. Mukhametzyanov; Boris N. Solomonov (Molecules, 2024)
1,3,5-Tris-(α-naphthyl)benzene is an organic non-electrolyte with notable stability of an amorphous phase. Its glassy and supercooled liquid states were previously studied by spectroscopic and calorimetric methods. Despite the continuing interest in its amorphous state and, particularly, vapor-deposited glasses, the thermodynamic parameters of the vaporization of 1,3,5-tris-(α-naphthyl)benzene have not been obtained yet. Likewise, the reliable evaluation of the thermodynamic parameters of fusion below the melting point, required to establish the thermodynamic state of its glass, is still an unsolved problem. In this work, the heat capacities of crystalline and liquid phases, the temperature dependence of the saturated vapor pressures, fusion and vaporization enthalpies were determined using differential and fast scanning calorimetry and were verified using the estimates based on solution calorimetry. The structural features of 1,3,5-tris-(α-naphthyl)benzene are discussed based on the computations performed and the data on the molecular refractivity. The consistency between the values obtained by independent techniques was demonstrated.